2014
DOI: 10.5455/jeos.20140924105123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbiological and physico-chemical quality of drinking water in North Gondar Zone, Northwest Ethiopia

Abstract: Introduction: Assessing the microbiological and physico-chemical quality of drinking water sources is important to protect public health. Little is known about the microbiological and physico-chemical quality of drinking water in North Gondar Zone. Therefore, this study was aimed to assess the microbiological and physico-chemical quality of drinking water sources in North Gondar Zone, Northwest Ethiopia. Methods: A cross-sectional study was conducted from April to May 2014 in seven districts (Chilga, Debark, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The results showed that average temperature records of the water samples range from 20.5 to 20.8 C without showing significant difference among the sources (Table 1). Similarly, earlier studies in Gondar zone [12] and Bahir Dar [17] reported a mean temperature of 21.3 C and 23.8 C, respectively. In tropics, the climate is characterized by high temperature and rainfall, and these factors might have contributed to the high temperature records of water samples from different cities of Ethiopia that did not meet the WHO standard of <15 C [18].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The results showed that average temperature records of the water samples range from 20.5 to 20.8 C without showing significant difference among the sources (Table 1). Similarly, earlier studies in Gondar zone [12] and Bahir Dar [17] reported a mean temperature of 21.3 C and 23.8 C, respectively. In tropics, the climate is characterized by high temperature and rainfall, and these factors might have contributed to the high temperature records of water samples from different cities of Ethiopia that did not meet the WHO standard of <15 C [18].…”
Section: Resultssupporting
confidence: 73%
“…Our results showed that the temperature of the tap water samples ranged between 16.8°C and 22.1°C without showing any significant difference among the sites (Table 3) and hence did not meet the WHO standard of <15°C [18]. Likewise, similar earlier studies [8, 12] reported higher temperature values in drinking water from different Ethiopian cities. The pH of tap water samples varied from 6.6 to 7.0 (Table 3) without any significance among the sampling points.…”
Section: Resultssupporting
confidence: 50%
“…Similarly, studies conducted in the different localities of Ethiopia such as in Bahir Dar town [ 8 ], Dire Dawa [ 20 ], north Gonder [ 21 ], Jimma town [ 7 ], Sidama Zone [ 9 ], Shambu town [ 22 ], and Nekemte town [ 12 ] have shown a high level of coliform counts that did not meet the WHO permissible level. This implies that bacterial contamination of drinking water continues to be a public health concern in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The materials used to store water at home for days are highly suitable for the growth of anaerobic organisms. Several studies conducted in Ethiopia on the physicochemical and bacteriological quality of drinking water from various sources indicated that water sources were contaminated with pollution indicators such as fecal and total coliforms (APHA 1998; Mengesha et al 2004;Birhanu 2007;Temesgen & Hameed 2009;Milkiyas et al 2011;Solomon et al 2011;Debasu et al 2014;Yasin et al 2015;Gonfa et al 2019;Alemnew & Seyoum 2020;Matusala et al 2020).…”
Section: Introductionmentioning
confidence: 99%